Grammaticality and idiomaticity of English monolinguals and English bilinguals in a semi-naturalistic setting - Gomari, Hamid (Animo Repository, 2015)
A two-phase, sequential, explanatory, mixed-methods design was used to investigate English monolingual students (EMs) and English bilingual student (EMs) grammaticality and idiomaticity in a semi-naturalistic setting. Four hundred seventy-five high school students of mixed gender (262 females and 213 males) and ethnicity from an international school in the Philippines participated in the study. The participants were from grades 9 to 12, and their ages ranged from 13 to 19 (M = 15.86). They were from varied cultural and ethnic backgrounds39 different nationalities were represented in the sample. Phase 1 employed a quantitative, cross-sectional, exploratory non-experimental design, and phase 2 employed a multiple-case study design enabling an in-depth understanding of students˜ subjective experiences in relation to grammaticality and idiomaticity (N = 12). In the quantitative phase, first, an independent samples t-test was conducted to examine the difference between the performance of EMs (N = 195) and EBs (N = 280) in grammar, nativelike selections (NLSs), and situation-bound utterances (SBUs) tests, and the results showed that EMs significantly outperformed EBs. Second, Pearson's correlation coefficients were used to investigate the intercorrelations among all the variables in both EMs and EBs groups, and the results indicated that the variables of language contact (LC), length of exposure (LoE), integrative motivation (Int.M), and age of L2 onset (AoA) were significantly related to EBs —knowledge of grammar, NLS and SBU. Age of L2 onset was the only variable which was negatively correlated with grammaticality and idiomaticity. Besides, EBs knowledge of grammar and idiomatic expressions (NLS and SBU) were significantly correlated with their English academic performance (EAP) however, no significant correlation was found between EMs knowledge of grammar and idiomatic expressions and their EAP. ii Lastly, multiple regression analysis was conducted to investigate the factors predicting grammaticality and idiomaticity among EBs, and the possible impacts of knowledge of grammar, NLS, and SBU on English academic performance were examined in both EMs and EBs groups. The results revealed that the variables of LC, LA, and Int.M predicted English bilinguals knowledge of grammar and idiomatic expressions (NLS and SBU); however, LoE was found to be the predictor of knowledge of grammar but not that of idiomatic expressions. Furthermore, EMs knowledge of grammar and idiomatic expressions did not significantly impact on their EAP, but English bilinguals knowledge of grammar and knowledge of SBU (idiomaticity at discourse level) significantly impacted on their EAP. The findings of the qualitative phase to some extent confirmed the findings of the quantitative strand and supported the results of regression analysis as regards the impacts of LC and LA on grammaticality and idiomaticity, but Int.M which was found to be a negative predictor was reported by two EBs to be a positive predictor of both grammaticality and idiomaticity. Moreover, LoE was reported by several students to be a positive predictor of idiomaticity, and the majority of the EBs asserted that LoE impacts on their knowledge of grammar as well. The impacts of grammaticality on EAP were affirmed by the majority of the participants, and idiomaticity was reported by several students (EMs and EBs) to moderately impact on their EAP. The findings of the quantitative and qualitative strands were integrated and discussed in terms of their implications for EMs and EBs in the international school setting.